Invisible Children - Ajmera, Maya. author. aut Link
XXIII, 304 p.
Keywords: 'This masterful volume is remarkable in its scope and depth. It calls attention to the countless children globally who are exposed to poverty and other adversities. Emphasizing the shortcomings of many traditional efforts and recommending innovative grass-roots approaches that promise high impact, it offers excellent guidance for anyone involved in foreign assistance or international development.' –Jo Boyden, University of Oxford, UK ‘Invisible Children provides a passionate, comprehensive and well-researched overview of community-based organizations and the vital contribution they make toward the wellbeing of the most vulnerable children globally. This book is a valuable contribution to any international development course.’ -Peter Laugharn, The Hilton Foundation, USA Maya Ajmera and Greg Fields provide the architecture of a new perspective on the global agenda for children, based on a new global web of relationships stemming from thecommunity level. Arguing that the existing global agenda for children has failed, this book reimagines how society can support the world’s most vulnerable children. In doing so, Invisible Children identifies and gives voice to the millions of children globally living on society’s margins, while showing a way forward as to how we can best invest in children. .